Dealing with loss in the face of disasters and crises: Integrating interpersonal theories of couple adaptation and functioning. (February 2022) - Karantzas, Gery C.; Feeney, Judith A.; Agnew, Christopher R.; Christensen, Andrew; Cutrona, Carolyn E.; Doss, Brian D.; Eckhardt, Christopher I.; Russell, Daniel W.; Simpson, Jeffry A.
Abstract: The COVID-19 pandemic has highlighted the significant and varied losses that couples can experience during times of global and regional disasters and crises. What factors determine how couples navigate their close relationships during times of loss? In this paper, we elaborate and extend on one of the most influential frameworks in relationship science—the Vulnerability Stress Adaptation Model (VSAM, Karney and Bradbury, 1995)—to enhance the model's power to explain relationships during loss-themed disasters/crises. We do so by elaborating on attachment theory and integrating interdependence theory (emphasizing partner similarities and differences). Our elaboration and extension to the VSAM provides a comprehensive framework to guide future research and inform practice and policy in supporting relationships during and beyond loss-themed disasters/crises. Highlights: Attachment insecurity is a key vulnerability factor for when couples face loss-themed crises/disasters. Partner similarities and differences are critical to understanding couple adaptation. The model has implications for research, policy, and practice in times of loss.